Errores refractivos y su influencia en la calidad de vida en estudiantes con diversidad funcional de la “Unidad Educativa Nuestra Señora Del Carmen” Ricaurte- Los Ríos, octubre 2024 - abril 2025. - Cedeño Bajaña, Hanny Scarlet (2025)
The general objective was to determine refractive errors and their influence on the quality of life in students with functional diversity of the Educational Unit Our Lady of Carmen Ricaurte – The rivers, October 2024 – March 2025. The instruments used were: clinical history, optometric instruments such as: test box, retinoscope, schiascopic rulers, occluder, number and figure optotypes, millimetric ruler and flashlight, SREEQ-R questionnaire. Having a population of 80 students of the institution and the sample collected was of 47 students with refractive error where in the results a prevalence was found in its majority being hyperopia with 45%, myopia 36% and finally astigmatism with 19% and regarding the quality of life the students showed difficulties to see the blackboard, distant and near things.